أثر القرآن الكريم في نشأة العلوم اللغوية - حاقة, عبد الكريم (جامعة الوادي - University of Eloued, 2018)
يهدف هذا البحث إلى بيان دور القرآن الكريم في ظهور العلوم اللغوية ونشأتها، فقبل نزول القرآن الكريم لم يكن للعرب اهتمام كبير بتقنين لغتهم، إذ كانوا يتكلمون لغتهم بالسليقة ويفهمونها كذلك، ولكنهم اختلطوا بغيرهم من الأمم بعد الإسلام، وظهر فيهم اللحن، واحتاجوا إلى معرفة اللغة العربية ليفهموا أساليب القرآن التعبيرية، وكان أول العلوم ظهورا علم التفسير، إذ ابتدأ هذا العلم في حياة النبي ـ ـ ثم تتابعت العلوم الأخرى، فظهر علم النحو والصرف، وكان في بدايته مختلطا بعلم الأصوات، ثم ظهر علم الدلالة وتأليف المعاجم اللغوية، وهكذا نلاحظ كيف كان اهتمام العرب بلغتهم خدمة للقرآن الكريم، وهذا ما قصدنا إلى تجليته في هذا البحث الذي أردنا أن نجيب فيه عن الإشكالات الآتية: ما مميزات اللغة القرآنية؟ وما العلوم اللغوية التي كان القرآن الكريم سببا في ظهورها؟ وما أثر القرآن الكريم في اللغة العربية؟ This research aims to explain the role of the Holy Qur’an in the emergence of linguistic sciences. Arabs did not have a great interest in codifying their language before the revelation of the Qur’an, and when they mixed with other nations, error appeared in speech, and they needed knowledge of the Arabic language in order to understand the methods of the Qur’an, and the science of exegesis was the first to emerge. Which began with the mission of the Prophet, may God’s prayers and peace be upon him, and then the other sciences followed, then grammar and morphology appeared, then semantics and the compilation of linguistic dictionaries appeared, and this is how the interest of the Arabs in their language began to serve the Holy Qur’an, and this is what we wanted to explain in this research in the answer to the following problems: What are the advantages of the Quranic language? What are the linguistic sciences that the Holy Quran was the cause of its emergence? What is the effect of the Holy Qur’an on the Arabic language?
مقال
Keywords: القرآن الكريم؛ علوم اللغة؛ النحو؛ البلاغة؛ علم الأصوات; The Holy Quran; Language Science; Grammar; Rhetoric; phonetics